Mosses of Daqahlia Province with one new record for Africa and three new records for Egypt (Bangladesh Journal of Plant Taxonomy, 2021)
Thirty six moss species were recorded from Daqahlia province, Nile Delta. Weissia perligulata Flow. (Pottiaceae) was new record to Afr1. In addition, Hyophila involute (Hook.) Jaeg., (Pottiaceae), Ptychostomum arcticum (R. Brown) J. R. Spence ex Holyoak & N. Pederson and P. cyclophyllum (Schwagr) J. R. Spence (Bryaceae) were new records for Egypt. Fifteen species were new to Nile delta. This raised the number of identified moss taxa recorded from Egypt up to 192 taxa, from Nile delta 51 taxa and Daqahlia province 39 taxa. Data on the up-to-date classification, habitats, voucher specimens and distribution of the enumerated species and the descriptions of the new records including the photos have been provided.Bangladesh J. Plant Taxon. 28(1): 257-270, 2021 (June)